1995
DOI: 10.1128/jcm.33.5.1075-1079.1995
|View full text |Cite
|
Sign up to set email alerts
|

PCR for detection of rubella virus RNA in clinical samples

Abstract: A reverse transcription nested PCR (RT-PCR) assay for the detection of rubella virus RNA using primers from the E1 open reading frame was established. This assay was found to be sensitive (detecting approximately two synthetic RNA copies and RNA extracted from 0.1 50% tissue culture infective dose of rubella virus) and specific; five wild-type rubella strains and four vaccine strains were detected, and no nonspecific amplification of 16 other RNA viruses or RNAs from seven cell types occurred. Rubella virus RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(22 citation statements)
references
References 21 publications
0
20
0
2
Order By: Relevance
“…Although several investigators have reported the development of RV RT-PCR with a view to its use for prenatal diagnosis of CAR (7,9,16), there has been only one published preliminary report of its use for this purpose (24). Our RT-PCR has been shown to compare well with virus isolation for detection of RV in pharyngeal swabs and POCs (7). In the larger series of POCs presented here, we obtained evidence of intrauterine infection by RT-PCR in 67% of cases in which primary infection had occurred in the first 12 weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several investigators have reported the development of RV RT-PCR with a view to its use for prenatal diagnosis of CAR (7,9,16), there has been only one published preliminary report of its use for this purpose (24). Our RT-PCR has been shown to compare well with virus isolation for detection of RV in pharyngeal swabs and POCs (7). In the larger series of POCs presented here, we obtained evidence of intrauterine infection by RT-PCR in 67% of cases in which primary infection had occurred in the first 12 weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of RV RNA by RT-PCR. RV RNA was detected by a previously described RT-PCR (7), which has been shown to be specific for RV RNA and sufficiently sensitive to detect 0.1 50% tissue culture infectious dose or approximately two synthetic RNA copies. The oligonucleotides used were located within the E1 open reading frame of the RV genome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nested RT-PCR based diagnosis is awardable on amniotic fluid, urine, fetal blood or mother's blood. 13 Using these primers (first round R2 -5'CAA CAC GCC GCA CGG ACA AC 3' -8807-8826, R7 4'CCA CAA GCC GCG AGC AGT CA 3' -8991-8972. Nested R11 -5' CTC GAG GTC CAG GTC CYG CC 3' 8826-8845.…”
Section: Serodiagnosismentioning
confidence: 99%
“…Nested R11 -5' CTC GAG GTC CAG GTC CYG CC 3' 8826-8845. R8C -5' GAA TGG CGT TGG CAA ACC GG 3' 8968-8949), authors 13 have demonstrated that the method was highly specific amplifying all the nine strains of rubella virus (including 4 vaccine strains). No false positive PCR products were generated from the RNAs of 16 other RNA viruses or RNAs from 7 cell types or human DNA.…”
Section: Serodiagnosismentioning
confidence: 99%